Influence of sinter-hardening on microstructures and mechanical properties of Astaloy Mo-based steels - Gunen, Mehmet; Bakkaloglu, Adem (ELSEVIER, 2019)
In this study, the influence of sinter-hardening process on Astaloy Mo based powder metallurgical steels was investigated. In line with this purpose, diffusion alloyed Distaloy DH (Astaloy Mo-2 wt% Cu) with 0,6 wt% C, Astaloy Mo with 2 wt% Cu-0,6 wt% C, and Astaloy Mo with 1 wt% Cu-0,6 wt% C powder mixes were chosen. Due to these compositions, the effects of copper amounts, cooling rates and prealloying methods on mechanical properties and microstructures of mentioned powders were examined. Aim of the work was to determine the proper parameters for Fe-Mo-Cu-C alloys in order to be able to use them more common in automotive industry. In line with this objective, transverse rupture strength, tensile strength and microhardness tests and also microscopical investigations were performed. In consequence of the experimental studies, it was observed that increase of cooling rate led to transformation of bainite to martensite and increase of hardness. However, increasing cooling rate caused decreases in the strength values of all specimens. Besides, it was determined that Distaloy DH specimens had better strength values owing to having less porous structure and smaller pores in comparison to other specimens. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Metals and alloys; Sintering; Sinter-hardening; Prealloying; Astaloy Mo; Distaloy DH; Materials Science; Physics